2021
DOI: 10.1163/15691497-12341576
|View full text |Cite
|
Sign up to set email alerts
|

Joining the Global Environmental Protection Movement: an Exploration of Public Environmental Concern in the UAE

Abstract: This study explores levels of concern about the environment in the United Arab Emirates (UAE). Data for the study were obtained from the 2019 ‘Levels of Concern about the Environment in the UAE’ survey. A convenience sample of 1520 respondents were selected, contacted and interviewed by research assistants. Per the study’s findings, respondents did endorse three out of five dimensions of the Revised NEW Ecological Paradigm scale including the anthropocentric view of nature, balance of nature, and the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Related studies also mentioned environmental concerns including the following. Balance of Nature, which refers to the individual's belief that the balance of nature is highly vulnerable to disruption by human activities [63]; Limit to Growth, which refers to the individual's belief that the resources that exist on Earth are limited [64]; Anti anthropocentrism, which refers to the idea that nature not only satisfies human needs but also the needs of other organisms [65]; anti-exemptionalism, which refers to the belief that human life cannot be separated from the rules and laws of nature [66]; and eco-crisis, which refers to the belief that humans are causing harmful effects on the physical environment. is the belief that humans are causing harmful damage to the physical environment [67].…”
Section: Environmental Concernsmentioning
confidence: 99%
“…Related studies also mentioned environmental concerns including the following. Balance of Nature, which refers to the individual's belief that the balance of nature is highly vulnerable to disruption by human activities [63]; Limit to Growth, which refers to the individual's belief that the resources that exist on Earth are limited [64]; Anti anthropocentrism, which refers to the idea that nature not only satisfies human needs but also the needs of other organisms [65]; anti-exemptionalism, which refers to the belief that human life cannot be separated from the rules and laws of nature [66]; and eco-crisis, which refers to the belief that humans are causing harmful effects on the physical environment. is the belief that humans are causing harmful damage to the physical environment [67].…”
Section: Environmental Concernsmentioning
confidence: 99%
“…A review of relevant literature shows that scientific research on water consumption behaviors in the UAE, or even in the Middle East and North Africa (MENA) more generally is rare (Alibeli & Nair, 2021; Ghneim, 2010). Asakawa (2004) observed that with few exceptions water consumption behavior has not been a common topic of research in conventional analyses of water consumption or consumer behavior.…”
Section: Justification Of the Studymentioning
confidence: 99%
“…An improved understanding of water consumption behavior, particularly in the UAE where less literature is available, is therefore critical, and forms the focus of this research. The cultural and ethnic diversity of the UAE (Alibeli & Nair, 2021; Yaghi & Yaghi, 2013), offers an opportunity to gain a comprehensive and inclusive understanding of water consumption behavior in different cultures which can then inform campaign planning and implementation of programs aiming to change water consumption behavior.…”
Section: Justification Of the Studymentioning
confidence: 99%
“…Many surveys were developed using theoretical approaches based on models such as Ecological Values and the NEP. Being a widely used scale, NEP consists of five dimensions, balance of nature, eco-crisis, anti-exemptionalism, limits to growth and anti -anthropocentrism (known as human domination) (Dunlap & Jones, 2002;Kopnina, 2011;Alibeli & Nair, 2021). Balance of nature is the awareness that human activity affects nature's balance.…”
Section: Introductionmentioning
confidence: 99%